Role of microstructure in oxygen induced photodegradation of methylammonium lead triiodide perovskite films - Sun, Qing; Faßl, Paul; Becker-Koch, David; Bausch, Alexandra; Rivkin, Boris; Hopkinson, Paul E.; Vaynzof, Yana (Advanced energy materials, 2017)
This paper investigates the impact of microstructure on the degradation rate of methylammonium lead triiodide (MAPbI3) perovskite films upon exposure to light and oxygen. By comparing the oxygen induced degradation of perovskite films of different microstructure-fabricated using either a lead acetate trihydrate precursor or a solvent engineering technique-it is demonstrated that films with larger and more uniform grains and better electronic quality show a significantly reduced degradation compared to films with smaller, more irregular grains. The effect of degradation on the optical, compositional, and microstructural properties of the perovskite layers is characterized and it is demonstrated that oxygen induced degradation is initiated at the layer surface and grain boundaries. It is found that under illumination, irreversible degradation can occur at oxygen levels as low as 1%, suggesting that degradation can commence already during the device fabrication stage. Finally, this work establishes that improved thin-film microstructure, with large uniform grains and a low density of defects, is a prerequisite for enhanced stability necessary in order to make MAPbI3 a promising long lived and low cost alternative for future photovoltaic applications.
First published: 14 July 2017
Gesehen am 18.06.2018